Chromium-zirconium-copper contact surface cleaning solution, preparation method thereof and chromium-zirconium-copper contact surface cleaning method
By using a chromium zirconium copper contact surface cleaning solution containing organic sulfonic acid, inorganic strong acid and nonionic surfactant, the problem of difficult removal of chromium zirconium copper contact oxide scale in the prior art is solved, and an efficient and economical cleaning effect is achieved.
Patent Information
- Application Number
- CN202411686850.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art is difficult to efficiently remove the oxide scale formed on the surface of chromium zirconium copper contacts, especially after strong pickling. The traditional method has problems such as low production efficiency, inconvenient operation and re-adhesion of the oxide scale.
A chromium zirconium copper contact surface cleaning solution is provided, which contains 1%-10% organic sulfonic acid, 1%-5% inorganic strong acid and 1%-3% nonionic surfactant, and the oxide scale is removed by soaking and rolling and throwing.
This cleaning solution can efficiently remove the scale on the surface of chromium zirconium copper contacts, improve the cleaning efficiency and product quality, and avoid the problem of scale reattachment.
Smart Images

Figure CN119640272A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of contact surface treatment, and in particular to a chromium-zirconium-copper contact surface cleaning liquid and a preparation method thereof, and a chromium-zirconium-copper contact surface cleaning method. Background Art
[0002] The chemical composition (mass fraction) of chromium-zirconium copper (CuCrZr) is % (Cr0.3-0.8, Zr0.3-0.6). It has good electrical conductivity, thermal conductivity, high hardness, wear resistance, anti-cracking, crack resistance and high softening temperature, less electrode loss during welding, fast welding speed, low total welding cost, etc. It is widely used in welding, conductive nozzles, switch contacts, mold blocks, welding auxiliary devices and other auxiliary materials in the machinery manufacturing industry. Among them, the silver-copper composite contacts of relays have the advantages of saving silver consumption in contact processing, flat silver layer and long electrical life of relays compared with red copper materials. Chromium-zirconium copper has good comprehensive performance and has good development prospects in the field of relay contacts.
[0003] During the cold heading process of contacts, due to factors such as processing equipment and product structure, the edges of the contact copper caps have burrs of varying degrees. During the contact cleaning process, a planetary high-speed grinder is conventionally used to remove the burrs. While removing the burrs, the contact silver surface will also cause copper powder residue due to friction. In order to remove the copper powder, the most commonly used method in the industry is sulfuric acid-hydrogen peroxide system pickling. However, this system reacts chemically with the chromium and zirconium in the copper alloy to produce chromium oxide and zirconium oxide while removing the copper powder. The copper base surface of the contact is severely oxidized and discolored. Subsequent conventional activation cannot remove the oxide scale on the surface. Therefore, a new cleaning fluid is needed to remove the oxide scale formed on the chromium-zirconium copper surface.
[0004] In addition, the oxide scale formed by strong acid pickling of chromium, zirconium and copper in the industry is mainly removed by magnetic polishing, which mainly uses steel needles to cut and grind to remove the oxide scale on the surface under the action of a magnetic field. This method can also effectively remove the oxide scale, but this method has low production efficiency and is inconvenient to operate. At the same time, for contacts with larger specifications, the copper powder treated by this method will re-attach to the silver surface of the contacts, affecting product quality.
[0005] At present, a patent application with publication number CN1261630A discloses a pickling solution, which is mainly added with electrolyte used in a sodium sulfate pickling line, and is optimized by adding divalent and trivalent iron salts, etc. However, this pickling solution can only be used for cleaning ferroalloys, and requires additional application of current, and the process is complicated; in addition, another patent application with publication number CN110129810A discloses a chromium-zirconium-copper alloy surface cleaning solution, which is mainly composed of sulfuric acid, hydrochloric acid, hydrogen peroxide, etc., and its immersion time is 1-30s. The surface oxide scale is removed by immersing the chromium-zirconium-copper alloy, but this acid solution can only remove slight oxide scale and is not suitable for surfaces where severe oxide scale has formed. Summary of the invention
[0006] Aiming at the problem that the oxide scale formed on the chromium-zirconium-copper contact after strong acid washing is difficult to remove, the present invention provides a chromium-zirconium-copper contact surface cleaning liquid and a preparation method thereof, and a chromium-zirconium-copper contact surface cleaning method.
[0007] In order to solve the above technical problems, one of the objects of the present invention is to provide a chromium-zirconium-copper contact surface cleaning solution, which comprises, by volume percentage: 1%-10% of organic sulfonic acid, 1%-5% of inorganic strong acid, 1%-3% of non-ionic surfactant, and the remainder is water.
[0008] In one embodiment, the chromium-zirconium-copper includes, by mass percentage, 0.3%-0.8% chromium and 0.3%-0.6% zirconium.
[0009] In one embodiment, the organic sulfonic acid is methanesulfonic acid, and the inorganic strong acid is sulfuric acid.
[0010] In one embodiment, the volume percentage of the methanesulfonic acid is higher than the volume percentage of the sulfuric acid.
[0011] In one embodiment, the nonionic surfactant is octylphenol polyoxyethylene ether.
[0012] In one embodiment, the cleaning solution is composed of the following components, measured by volume percentage: 3% sulfuric acid, 1%-10% methylsulfonic acid, 2% octylphenol polyoxyethylene ether, and the balance is water.
[0013] In one embodiment, the cleaning solution is composed of the following components, measured by volume percentage: 3% sulfuric acid, 5% methyl sulfonic acid, 2% octylphenol polyoxyethylene ether, and the balance is water.
[0014] The second object of the present invention is to provide a method for preparing a chromium-zirconium-copper contact surface cleaning solution, comprising the following steps:
[0015] The following components are weighed and mixed by volume percentage: 1%-5% of inorganic strong acid, 1%-10% of organic sulfonic acid, 1%-3% of non-ionic surfactant, and the balance is water.
[0016] The third object of the present invention is to provide a surface cleaning method for chromium-zirconium-copper contacts, comprising the following steps:
[0017] The chromium-zirconium-copper contacts that have been oxidized and discolored after pickling are placed in a loading fixture;
[0018] Immersing a loading jig containing chromium-zirconium-copper composite contacts in a surface cleaning solution for cleaning;
[0019] After cleaning, take it out and wash it in water and dry it;
[0020] The surface cleaning liquid adopts the chromium-zirconium-copper contact surface cleaning liquid as described above.
[0021] In one embodiment, the cleaning comprises tumbling at a rotation speed of 15-30 rpm for 30 minutes at room temperature.
[0022] Based on the above, compared with the prior art, the chromium-zirconium-copper contact surface cleaning liquid provided by the present invention can efficiently remove oxide scale.
[0023] Other features and beneficial effects of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other beneficial effects of the present invention can be realized and obtained by the structures particularly pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 This is a photo of the surface appearance of the chromium zirconium copper contact product A which turned black after being treated with a sulfuric acid-hydrogen peroxide system;
[0026] Figure 2 This is a photo of the surface appearance of the chromium zirconium copper contact product B which turned black after being treated with the sulfuric acid-hydrogen peroxide system;
[0027] Figure 3 A photograph of the surface appearance of the chromium-zirconium-copper contact after cleaning provided in Example 1 of the present invention;
[0028] Figure 4 A photograph of the surface appearance of the chromium-zirconium-copper contact after cleaning provided in Example 2 of the present invention;
[0029] Figure 5 A photograph of the surface appearance of the chromium-zirconium-copper contact after cleaning provided in Example 6 of the present invention;
[0030] Figure 6 A photograph of the surface appearance of the chromium-zirconium-copper contact after cleaning provided in Comparative Example 1 of the present invention;
[0031] Figure 7 A photograph of the surface appearance of the chromium-zirconium-copper contact after cleaning provided in Comparative Example 2 of the present invention;
[0032] Figure 8 A photograph of the surface appearance of the chromium-zirconium-copper contact after cleaning provided in Comparative Example 3 of the present invention;
[0033] Fig. 9 This is a photo of the surface appearance of the chromium-zirconium-copper contact after cleaning provided in Comparative Example 4 of the present invention. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments; the technical features designed in different implementation modes of the present invention described below can be combined with each other as long as they do not conflict with each other; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0035] In the description of the present invention, it should be noted that all terms used in the present invention (including technical terms and scientific terms) have the same meanings as those generally understood by ordinary technicians in the field to which the present invention belongs, and cannot be understood as limiting the present invention; it should be further understood that the terms used in the present invention should be understood to have the same meanings as these terms in the context of this specification and in the relevant fields, and should not be understood in an idealized or overly formal sense, unless explicitly defined in the present invention.
[0036] The embodiment of the present invention provides a chromium-zirconium-copper contact surface cleaning liquid.
[0037] In some embodiments, the chromium-zirconium-copper comprises, by mass percentage, 0.3%-0.8% chromium and 0.3%-0.6% zirconium;
[0038] In some embodiments, the chromium zirconium copper contact surface cleaning solution comprises:
[0039] (1) Organic sulfonic acid; preferably, the organic sulfonic acid is methanesulfonic acid, because the oxide film structure on the surface of the chromium-zirconium-copper alloy is very fatal, and the reducing and acidic properties of methanesulfonic acid can effectively destroy the structure of the oxide film.
[0040] Further, the volume percentage of the organic sulfonic acid in the surface cleaning solution is 1%-10%, and the volume percentage of the organic sulfonic acid can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., or any point value between the above two; preferably, the volume percentage of the organic sulfonic acid is 5%; wherein, the concentration of methanesulfonic acid has a crucial influence on the cleaning effect; when the concentration of methanesulfonic acid is moderate, the cleaning solution can quickly and effectively remove the oxide scale on the surface of the chromium-zirconium-copper alloy, and will not cause excessive corrosion to the metal itself. Although further increasing the concentration of methanesulfonic acid can accelerate the removal speed of the oxide scale, when the concentration of methanesulfonic acid is too high, its strong corrosiveness is easy to cause excessive corrosion to the metal, resulting in an increase in the roughness of the metal surface, and even affecting the mechanical properties and electrical conductivity of the metal, and when the concentration of methanesulfonic acid is too low, the surface cleaning solution has a poor cleaning effect on the oxide scale of the chromium-zirconium-copper alloy, and the cleaning speed is slow, and the effect is not obvious.
[0041] (2) Inorganic strong acid; preferably, the inorganic strong acid is sulfuric acid; as an inorganic strong acid, sulfuric acid has good solubility and oxidizability, and can help decompose and remove stubborn stains and oxides on the metal surface. When used in combination with organic sulfonic acid (methanesulfonic acid), the overall acidity and reactivity of the cleaning solution can be enhanced, thereby improving the cleaning efficiency and effectively removing the oxide scale on the surface of the chromium-zirconium-copper contact.
[0042] Furthermore, the volume percentage of the inorganic strong acid in the surface cleaning liquid is 1%-5%, and the volume percentage of the inorganic strong acid can specifically be 1%, 2%, 3%, 4%, 5%, etc., or any point value between any two of the above; preferably, the volume percentage of the inorganic strong acid is 3%.
[0043] In some preferred embodiments, the volume percentage of the methanesulfonic acid is higher than the volume percentage of the sulfuric acid.
[0044] (3) Non-ionic surfactant; preferably, the non-ionic surfactant is octylphenol polyoxyethylene ether; the octylphenol polyoxyethylene ether (OPEO) has a relatively long alkyl chain and polyoxyethylene ether group, and this structure makes it have high chemical stability and is not easily destroyed under strong acid conditions, so that it can show better performance in cleaning solutions containing methanesulfonic acid and sulfuric acid.
[0045] Furthermore, the volume percentage of the non-ionic surfactant in the surface cleaning solution is 1%-3%; the volume percentage of the non-ionic surfactant can specifically be 1%, 2%, 3%, etc., or a point value between any two of the above; preferably, the volume percentage of the non-ionic surfactant is 2%.
[0046] (4) The balance is water.
[0047] In some preferred embodiments, the cleaning solution is composed of the following components, measured by volume percentage: 3% sulfuric acid, 1%-10% methylsulfonic acid, 2% octylphenol polyoxyethylene ether, and the balance is water.
[0048] In some preferred embodiments, the cleaning solution is composed of the following components, measured by volume percentage: 3% sulfuric acid, 5% methanesulfonic acid, 2% octylphenol polyoxyethylene ether, and the balance is water.
[0049] The embodiment of the present invention provides a method for preparing a chromium-zirconium-copper contact surface cleaning liquid, comprising the following steps: weighing and mixing the following components by volume percentage: 1%-5% of an inorganic strong acid, 1%-10% of an organic sulfonic acid, 1%-3% of a non-ionic surfactant, and the remainder being water.
[0050] The embodiment of the present invention also provides a surface cleaning method of a chromium-zirconium-copper contact, comprising the following steps:
[0051] Step 1, placing the chromium-zirconium-copper contacts that have been oxidized and discolored after pickling in a loading fixture;
[0052] Step 2, immersing the loading fixture containing the chromium-zirconium-copper composite contacts in a surface cleaning liquid for cleaning;
[0053] Step 3: Take out after cleaning and wash and dry in water;
[0054] Step 4: The surface cleaning liquid adopts the chromium-zirconium-copper contact surface cleaning liquid as described above.
[0055] In some preferred embodiments, the cleaning comprises tumbling at a rotation speed of 15-30 rpm for 30 minutes at room temperature.
[0056] The following examples and comparative examples are used to illustrate the present invention in more detail, but are not intended to limit the present invention in any way. In addition, unless otherwise specified, the raw materials used may also be conventional commercial products in the art, or may be prepared by conventional methods in the art.
[0057] The pretreatment of product A includes the following steps:
[0058] The chromium-zirconium-copper contact product to be treated is first placed in a stainless steel loading fixture with a mesh, and then placed in a 2L pickling solution with a volume percentage of 4% sulfuric acid, 3% hydrogen peroxide, and the balance being water. The acid temperature is 40°C, and the pickling treatment time is 90s. After the pickling is completed, two ultrasonic (frequency 40KHz power 500w) water washing is performed to obtain product A.
[0059] The pretreatment of product B includes the following steps:
[0060] The chromium-zirconium-copper contact product to be treated is first placed in a stainless steel loading fixture with a mesh, and then placed in a 2L pickling solution with a volume percentage of 4% sulfuric acid, 3% hydrogen peroxide, and the balance being water. The acid temperature is 40°C, and the pickling treatment time is 90s. After the pickling is completed, two ultrasonic (frequency 40KHz power 500w) water washing is performed to obtain product A.
[0061] Example 1
[0062] (1) Preparation of chromium-zirconium-copper contact surface cleaning solution
[0063] Weigh the raw materials according to the composition of the cleaning liquid, and prepare them by volume percentage: 5% of methanesulfonic acid, 3% of sulfuric acid, 2% of octylphenol polyoxyethylene ether, and the balance is water, and then select 1kg of chromium-zirconium-copper-silver composite contact product A. The preparation order is to first add sulfuric acid to the container, pre-mix methanesulfonic acid and octylphenol polyoxyethylene ether and then add them to sulfuric acid, and finally add water;
[0064] (2) Surface cleaning of chromium-zirconium-copper contacts
[0065] First, place the product in a stainless steel loading fixture with mesh, and then place the fixture and the product in the cleaning equipment. At room temperature, roll and tumble for 30 minutes at a rotation speed of 30 rpm. After tumbling, take it out and wash it with pure water, then dry it. After drying, observe the appearance of the contacts. Refer to Figure 3 shown.
[0066] Example 2
[0067] (1) Preparation of chromium-zirconium-copper contact surface cleaning solution
[0068] Weigh the raw materials according to the composition of the cleaning liquid, and prepare them by volume percentage: 5% of methanesulfonic acid, 3% of sulfuric acid, 2% of octylphenol polyoxyethylene ether, and the balance is water, and then select 1kg of chromium-zirconium-copper-silver composite contact product B. The preparation order is to first add sulfuric acid to the container, pre-mix methanesulfonic acid and octylphenol polyoxyethylene ether and then add them to sulfuric acid, and finally add water;
[0069] (2) Surface cleaning of chromium-zirconium-copper contacts
[0070] First, place the product in a stainless steel loading fixture with mesh, and then place the fixture and the product in the cleaning equipment. At room temperature, roll and tumble at a rotation speed of 15 rpm for 30 minutes. After tumbling, take it out and wash it with pure water, then dry it. After drying, observe the appearance of the contacts. Refer to Figure 4 shown.
[0071] Example 3
[0072] (1) Preparation of chromium-zirconium-copper contact surface cleaning solution
[0073] Weigh the raw materials according to the composition of the cleaning liquid, and prepare them by volume percentage: 3% of methanesulfonic acid, 2% of sulfuric acid, 1% of octylphenol polyoxyethylene ether, and the balance is water, and then select 1kg of chromium-zirconium-copper-silver composite contact product A. The preparation order is to first add sulfuric acid to the container, pre-mix methanesulfonic acid and octylphenol polyoxyethylene ether and then add them to sulfuric acid, and finally add water;
[0074] (2) Surface cleaning of chromium-zirconium-copper contacts
[0075] First put the product into a stainless steel loading fixture with a mesh, and then put the fixture and the product into the cleaning equipment. At room temperature, roll and tumble at a rotation speed of 20rpm for 30 minutes. After tumbling, take it out and wash it with pure water, then dry it. After drying, observe the appearance of the contacts.
[0076] Example 4
[0077] (1) Preparation of chromium-zirconium-copper contact surface cleaning solution
[0078] Weigh the raw materials according to the composition of the cleaning liquid, and prepare them by volume percentage: 8% of methanesulfonic acid, 4% of sulfuric acid, 3% of octylphenol polyoxyethylene ether, and the balance is water, and then select 1kg of chromium-zirconium-copper-silver composite contact product A. The preparation order is to first add sulfuric acid to the container, pre-mix methanesulfonic acid and octylphenol polyoxyethylene ether and then add them to sulfuric acid, and finally add water;
[0079] (2) Surface cleaning of chromium-zirconium-copper contacts
[0080] First put the product into a stainless steel loading fixture with a mesh, and then put the fixture and the product into the cleaning equipment. Under room temperature, roll and tumble at a rotation speed of 30rpm for 30 minutes. After tumbling, take it out and wash it with pure water, then dry it. After drying, observe the appearance of the contacts.
[0081] Example 5
[0082] (1) Preparation of chromium-zirconium-copper contact surface cleaning solution
[0083] Weigh the raw materials according to the composition of the cleaning liquid, and prepare them by volume percentage: 6% of methanesulfonic acid, 3% of sulfuric acid, 2% of octylphenol polyoxyethylene ether, and the balance is water, and then select 1kg of chromium-zirconium-copper-silver composite contact product A. The preparation order is to first add sulfuric acid to the container, pre-mix methanesulfonic acid and octylphenol polyoxyethylene ether and then add them to sulfuric acid, and finally add water;
[0084] (2) Surface cleaning of chromium-zirconium-copper contacts
[0085] First put the product into a stainless steel loading fixture with a mesh, and then put the fixture and the product into the cleaning equipment. Under room temperature, roll and tumble at a rotation speed of 30rpm for 30 minutes. After tumbling, take it out and wash it with pure water, then dry it. After drying, observe the appearance of the contacts.
[0086] Example 6
[0087] (1) Preparation of chromium-zirconium-copper contact surface cleaning solution
[0088] Weigh the raw materials according to the composition of the cleaning liquid, and prepare them by volume percentage: 3% of methanesulfonic acid, 5% of sulfuric acid, 2% of octylphenol polyoxyethylene ether, and the balance is water, and then select 1kg of chromium-zirconium-copper-silver composite contact product A. The preparation order is to first add sulfuric acid to the container, pre-mix methanesulfonic acid and octylphenol polyoxyethylene ether and then add them to sulfuric acid, and finally add water;
[0089] (2) Surface cleaning of chromium-zirconium-copper contacts
[0090] First, place the product in a stainless steel loading fixture with mesh, and then place the fixture and the product in the cleaning equipment. At room temperature, roll and tumble for 30 minutes at a rotation speed of 30 rpm. After tumbling, take it out and wash it with pure water, then dry it. After drying, observe the appearance of the contacts. Refer to Figure 5 shown.
[0091] Comparative Example 1
[0092] (1) Preparation of chromium-zirconium-copper contact surface cleaning solution
[0093] Weigh the raw materials according to the composition of the cleaning liquid, and prepare them by volume percentage: 1.75% sulfuric acid, 0.06% hydrogen peroxide, and the balance water, then select 1kg of chromium-zirconium-copper-silver composite contact product B, and prepare them in the order of adding sulfuric acid to the container first, then adding hydrogen peroxide to the sulfuric acid, and finally adding water;
[0094] (2) Surface cleaning of chromium-zirconium-copper contacts
[0095] First, place the product in a stainless steel loading fixture with mesh, and then place the fixture and the product in the cleaning equipment. At room temperature, roll and tumble for 30 minutes at a rotation speed of 30 rpm. After tumbling, take it out and wash it with pure water, then dry it. After drying, observe the appearance of the contacts. Refer to Figure 6 shown.
[0096] Comparative Example 2
[0097] (1) Preparation of chromium-zirconium-copper contact surface cleaning solution
[0098] Weigh the raw materials according to the composition of the cleaning liquid, and prepare them by volume percentage: 1.75% sulfuric acid, 0.06% hydrogen peroxide, and the balance water, then select 1kg of chromium-zirconium-copper-silver composite contact product B, and prepare them in the order of adding sulfuric acid to the container first, then adding hydrogen peroxide to the sulfuric acid, and finally adding water;
[0099] (2) Surface cleaning of chromium-zirconium-copper contacts
[0100] First, place the product in a stainless steel loading fixture with mesh, and then place the fixture and the product in the cleaning equipment. At room temperature, roll and tumble for 30 minutes at a rotation speed of 30 rpm. After tumbling, take it out and wash it with pure water, then dry it. After drying, observe the appearance of the contacts. Refer to Figure 7 shown.
[0101] Comparative Example 3
[0102] Please refer to Figure 8 The difference between this comparative example and Example 1 is that the cleaning solution is configured by volume percentage: 8% sulfuric acid, 2% octylphenol polyoxyethylene ether, and the balance is water.
[0103] Comparative Example 4
[0104] Please refer to Fig. 9 The difference between this comparative example and Example 1 is that the cleaning solution is configured by volume percentage: 8% of methanesulfonic acid, 2% of octylphenol polyoxyethylene ether, and the balance is water.
[0105] The appearance of the contacts after treatment of Examples 1-6 and Comparative Examples 1-4 is as follows:
[0106] Table 1
[0107] project Copper base color Example 1 Bright surface without oxide skin Example 2 Bright surface without oxide skin Example 3 Bright surface without oxide skin Example 4 Bright surface without oxide skin Example 5 Bright surface without oxide skin Example 6 Matt surface without oxidation skin Comparative Example 1 100% oxide scale remains on the surface Comparative Example 2 100% oxide scale remains on the surface Comparative Example 3 50% oxide scale remains on the surface Comparative Example 4 50% oxide scale remains on the surface
[0108] From the above results, it can be seen that the chromium zirconium copper contact surface cleaning solution provided by the present invention has a good light emitting effect on the chromium zirconium copper contacts that have turned black and discolored after being treated with a sulfuric acid-hydrogen peroxide system;
[0109] Specifically, by comparing Example 1 with Example 6, the volume percentage of the methanesulfonic acid is controlled to be higher than the volume percentage of the sulfuric acid, so that the prepared cleaning solution has a better light emission effect after treating the chromium-zirconium-copper contacts that have turned black and discolored after being treated with the sulfuric acid-hydrogen peroxide system; and Example 1 is compared with the cleaning solutions of Comparative Examples 1 and 2 based on the existing sulfuric acid & hydrogen peroxide cleaning system, and the cleaning solutions of Comparative Examples 3 and 4 respectively composed of monosulfuric acid and monomethylsulfonic acid. Due to the reducing and acidity of methanesulfonic acid, the structure of the oxide film can be effectively destroyed, and sulfuric acid has good solubility and oxidizability, which can help decompose and remove stubborn stains and oxides on the metal surface. When used in combination with an organic sulfonic acid (methanesulfonic acid), the overall acidity and reactivity of the cleaning solution can be enhanced, thereby improving the cleaning efficiency, effectively removing the oxide scale on the surface of the chromium-zirconium-copper contacts, and achieving a better light emission effect.
[0110] In addition, those skilled in the art should understand that, although there are many problems in the prior art, each embodiment or technical solution of the present invention can be improved in only one or several aspects, without having to solve all the technical problems listed in the prior art or background technology at the same time. Those skilled in the art should understand that the content not mentioned in a claim should not be used as a limitation on the claim.
[0111] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A chromium-zirconium-copper contact surface cleaning liquid, characterized in that: The surface cleaning liquid comprises, by volume percentage: 1%-10% of organic sulfonic acid, 1%-5% of inorganic strong acid, 1%-3% of non-ionic surfactant, and the remainder is water.
2. The chromium-zirconium-copper contact surface cleaning liquid according to claim 1, characterized in that: In terms of mass percentage, the chromium-zirconium-copper includes 0.3%-0.8% chromium and 0.3%-0.6% zirconium.
3. The chromium-zirconium-copper contact surface cleaning liquid according to claim 1, characterized in that: The organic sulfonic acid is methanesulfonic acid, and the inorganic strong acid is sulfuric acid.
4. The chromium-zirconium-copper contact surface cleaning liquid according to claim 3, characterized in that: The volume percentage of the methanesulfonic acid is higher than the volume percentage of the sulfuric acid.
5. The chromium-zirconium-copper contact surface cleaning liquid according to claim 4, characterized in that: The nonionic surfactant is octylphenol polyoxyethylene ether.
6. The chromium-zirconium-copper contact surface cleaning liquid according to claim 5, characterized in that: The cleaning solution is composed of the following components in volume percentage: 3% sulfuric acid, 1%-10% methylsulfonic acid, 2% octylphenol polyoxyethylene ether, and the balance is water.
7. The chromium-zirconium-copper contact surface cleaning liquid according to claim 5, characterized in that: The cleaning solution is composed of the following components in volume percentage: 3% sulfuric acid, 5% methylsulfonic acid, 2% octylphenol polyoxyethylene ether, and the balance is water.
8. A method for preparing a chromium-zirconium-copper contact surface cleaning solution, characterized in that: The following steps are involved: The following components are weighed and mixed by volume percentage: 1%-5% of inorganic strong acid, 1%-10% of organic sulfonic acid, 1%-3% of non-ionic surfactant, and the balance is water.
9. A surface cleaning method for chromium-zirconium-copper contacts, characterized in that: The following steps are involved: The chromium-zirconium-copper contacts that have been oxidized and discolored after pickling are placed in a loading fixture; Immersing a loading jig containing chromium-zirconium-copper composite contacts in a surface cleaning solution for cleaning; After cleaning, take it out and wash it in water and dry it; The surface cleaning liquid is the chromium-zirconium-copper contact surface cleaning liquid as described in any one of claims 1 to 7.
10. The surface cleaning method of chromium-zirconium-copper contacts according to claim 9, characterized in that: The cleaning includes tumbling at a rotation speed of 15-30 rpm for 30 minutes at room temperature.
Citation Information
Patent Citations
Chromium-zirconium-copper alloy surface cleaning solution
CN110129810A
Acid washing process for stainless steel
CN1261630A